Mahjar writers on the subject of Palestine - Hanley, Delinda C (The Washington report on Middle East affairs, 2017)
Doctor Edmund Ghareeb delivered the 2017 Hisham Sharabi Memorial Lecture at the Palestine Center/Jerusalem Fund in Washington DC on May 8. Ghareeb, who taught at American University for 28 years, as well as at Georgetown and George Washington universities in DC, is an internationally recognized expert on the Middle East, Kurds, Iraq and media issues. He discussed the contributions of early Arab-American "men of letters" of the Mahjar press, the general name for the early Arabic-language newspapers and publications published in the US from the 1890s to the 1920s.